2020
DOI: 10.1002/cc.20412
|View full text |Cite
|
Sign up to set email alerts
|

The Intersections of Race and Gender for Latina Midlevel Leaders

Abstract: This chapter provides a portrait of midlevel Latina leadership in community colleges, focusing on the intersections of gender and race. The chapter will also examine the challenges and barriers Latinas face as midlevel leaders, the role of mentors, as well as provide recommendations for community colleges to help increase the numbers of Latina leaders in their institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…From the start of this work, they knew they had buy‐in from senior leaders, resources from the Student Equity and Achievement Program, and an active commitment from campus colleagues. As Deans, they illustrated how midlevel leaders can successfully manage change efforts across organizational actors and served as an important link between institutional leaders and colleagues that would help put into practice a vision for improved transfer success (Garcia, 2020; McPhail & McPhail, 2020). They used data inquiry to uncover racial inequities, held community conversations on ways to address these barriers, and were advocates for using the equity policy's mandates to create more race‐conscious transfer strategies.…”
Section: Recommendations: Enacting Race‐conscious Change In Community...mentioning
confidence: 99%
“…From the start of this work, they knew they had buy‐in from senior leaders, resources from the Student Equity and Achievement Program, and an active commitment from campus colleagues. As Deans, they illustrated how midlevel leaders can successfully manage change efforts across organizational actors and served as an important link between institutional leaders and colleagues that would help put into practice a vision for improved transfer success (Garcia, 2020; McPhail & McPhail, 2020). They used data inquiry to uncover racial inequities, held community conversations on ways to address these barriers, and were advocates for using the equity policy's mandates to create more race‐conscious transfer strategies.…”
Section: Recommendations: Enacting Race‐conscious Change In Community...mentioning
confidence: 99%
“…As Latinx/a/o mid-level administrators attempt to navigate white power structures, they may feel limited in their ability to manage campus politics, although they will often accept additional burdens to address student demands and educate the campus about racially and ethnically minoritized student populations [25,26]. They are not only asked to manage their teams and resolve conflict but are also recruited to meet the demands of Latinx/a/o students on their campuses with limited organizational resources, even if that responsibility is not part of their position description [11].…”
Section: Latinx/a/o Student Affairs Administratorsmentioning
confidence: 99%
“…They are not only asked to manage their teams and resolve conflict but are also recruited to meet the demands of Latinx/a/o students on their campuses with limited organizational resources, even if that responsibility is not part of their position description [11]. Latinx/a/o administrators are often the only ones and/or the first Latinx/as/os in a mid-level role and experience tokenization throughout their careers [25][26][27]. They are often siloed into diversity-related functional areas, potentially limiting their access to future leadership opportunities [28].…”
Section: Latinx/a/o Student Affairs Administratorsmentioning
confidence: 99%
“…In a qualitative study of Latina executive leaders (including deans, vice presidents, provosts, and presidents), Valerde Pierce (2020) used testimonios to gather information on the types of advice or consejos they would give others who want to enter higher education administration. While some of the consejos they shared have been well-documented in the literature, such as developing a network of role models, mentors, and support structures (AAUW, 2016;Elenes, 2020;Garcia, 2020;Hill & Wheat, 2017;Montas-Hunter, 2012;Muñoz, 2010), the participants also highlighted the benefits of earning a doctorate, remaining authentic to who they are, and focusing on self-improvement and self-awareness. Findings reveal that higher education "promotes self-confidence and self-esteem, [as] it helps to address imposter syndrome and empowers individuals to feel that they belong in leadership" (Valerde Pierce, 2020, p.7).…”
Section: Women Leadersmentioning
confidence: 99%
“…One of the most significant supports that most participants recommended to other Latinas with a history of trauma was building a supportive community that can uplift you when you are struggling. Although many studies have identified the need for creating a network of mentors and role models, they have not specifically addressed how it may be an essential component of the success of leaders with trauma (AAUW, 2016;Elenes, 2020;Garcia, 2020;Hill & Wheat, 2017;Montas-Hunter, 2012;Muñoz, 2010). One participant explained that being intentional about creating a supportive community was necessary because, as a trauma survivor, it can be hard to ask for help, and based on the traumatic event, it can motivate individuals to be self-reliant.…”
Section: Significant Contributions Of the Studymentioning
confidence: 99%